2007
DOI: 10.1002/bem.20345
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to low‐level CW and GSM‐modulated 900 MHz radiofrequency does not affect Ba2+ currents through voltage‐gated calcium channels in rat cortical neurons

Abstract: We have studied the non-thermal effects of radiofrequency (RF) electromagnetic fields (EMFs) on Ba(2+) currents (I Ba 2+) through voltage-gated calcium channels (VGCC), recorded in primary cultures of rat cortical neurons using the patch-clamp technique. To assess whether low-level acute RF field exposure could modify the amplitude and/or the voltage-dependence of I Ba 2+, Petri dishes containing cultured neurons were exposed for 1-3 periods of 90 s to 900 MHz RF-EMF continuous wave (CW) or amplitude-modulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…No effects were observed from either the modulated or the CW exposures. Platano et al [2007] measured Ba 2þ current through voltage-gated calcium channels in primary rat cortical neurons and found no effects, irrespective of the signal used. Thorlin et al [2006] reported no effects from CWor GSM-modulated RF fields on Il6, Tnfa, Gfap and ED-1 levels in rat primary astroglial and microglial cells.…”
Section: Other Studiesmentioning
confidence: 99%
“…No effects were observed from either the modulated or the CW exposures. Platano et al [2007] measured Ba 2þ current through voltage-gated calcium channels in primary rat cortical neurons and found no effects, irrespective of the signal used. Thorlin et al [2006] reported no effects from CWor GSM-modulated RF fields on Il6, Tnfa, Gfap and ED-1 levels in rat primary astroglial and microglial cells.…”
Section: Other Studiesmentioning
confidence: 99%
“…This should be borne in mind, since some studies have shown that modulated RFR may cause neurological effects even at low average power [Bawin et al, 1975;Foster, 1996]. Others, however, show no such effect [e.g., Green et al, 2005;Platano et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The nervous system is one of the most studied systems under the action of exogenous electromagnetic fields (Espinosa et al, 2006 ; Marchionni et al, 2006 ; Platano et al, 2007 ; Apollonio et al, 2013 ; Di Lazzaro et al, 2013 ). Particularly, experimental and clinical studies that explore the effects of the stimulation of the Central Nervous System (CNS) with weak Magnetic Fields (MF) (i.e., with amplitude up to a few mT) and with a low frequency content (Extremely Low Frequency, ELF, 0–500 Hz) have yielded some evidence of functional changes in excitable biological tissues, as recently discussed in Di Lazzaro et al ( 2013 ).…”
Section: Introductionmentioning
confidence: 99%